#1

#2**+1 **

sorry Tertre the answer is incorrect the number needs to be a whole number

DarkCalculis
Apr 16, 2018

#5**+1 **

__5([x-1/2]-1) +2x __ = 5+x

3

Multiply both sides by 3

5 ( [ x - 1/2 ] - 1 ) + 2x = 3(5 + x)

5 ( x - 3/2) + 2x = 15 + 3x

5x - 15/2 + 2x = 15 + 3x

7x - 15/2 + 15 + 3x

4x = 15 + 15/2

4x = 45/2

x = (45/2) ( 1/4) = 45 / 8

CPhill Apr 16, 2018

#6**0 **

I'm sorry CPhill you are incorrect the answer is a whole number, not a fraction

DarkCalculis
Apr 16, 2018

#9**0 **

well I believe that everyone miss understood its x subtract 1 then divided by 2

__x-1__

2

DarkCalculis Apr 16, 2018

#10**+1 **

(5([x-1]/2-1)+2x)/3=5+x / multiply both sides by 3

5([x-1]/2-1)+2x=15+3x/ subtract 2x from both sides

5([x-1]/2-1)=2.5*x-7.5=15+x/ subtract (x-7.5) fdrom both sides

1.5*x=22.5 /divide both sides by 1.5

x=15

am i right?

ThePuppetMaster
Apr 16, 2018